Detection of hypoxemia and hyperoxemia by pulse oximetry in neonates and children - Sri Murni A. Ritonga; Ekawati Lutfia Haksari; Purnomo Suryantoro (Indonesian Pediatric Society Publishing House, 2016)
Objective To assess the validity of pulse oximetry for detecting hypoxemia and hyperoxemia in neonates and children. Methods This was a diagnostic test study conducted in Neonatal Intensive Care Unit (NICU). The subjects of the study were neonates of 0-28 days and children aged one month to 14 years in Pediatric Intensive Care Unit (PICU) of Sardjito Hospital. Hypoxemia and hyperoxemia were obtained by using NellcorR pulse oximetry, at the same time as blood gas analysis was obtained as a gold standard. Results There were 240 neonates and 268 children enrolled in this study. Pulse oximetry test with cut-off point 91% (neonates) and 90% (children) for detecting hypoxemia had sensitivity of 81% and 80%, specificity of 79% and 95% positive predictive value of 54% and 82% negative predictive value of93% and 93% positive likelihood ratio of 3. 79 and 14.20 and negative likelihood ratio of0.25 and 0.24. Pulse oximetry test with cut-off point 95% (neonates) and 97% (children) for detecting hyperoxemia had sensitivity of 7 8% and 81% specificity of 66% and 79%, positive predictive value of77% and 76% negative predictive value of 66% and 83% positive likelihood ratio of 2.26 and 3.84 and negative likelihood ratio of 0.34 and 0.24. Conclusion Pulse oximetry has a fairly good validity in detecting hypoxemia in neonates and children and in detecting hyperoxemia in children to however, it is not good enough to be used to detect hyperoxemia in neonates.